How variable is nitrogen in production agriculture fields?. Issue 3 (2nd September 2016) - Xiong, Xiong; Wilson, Eric; Fernández, Fabián G.
Abstract : Researchers set out to determine (i) the effect of drained and undrained conditions and previous crop on soil N concentrations and variability, (ii) the number of soil cores needed in a composite sample to correctly represent soil N fractions, and (iii) the feasibility of representing soil N in deeper layers of the soil with shallower samples. Earn 1 CEU in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/772 .